A Study of Language Variation Analysis - A Review - Tanvi Jangam,; Pratima Salunkhe, (International Journal of Scientific Research in Science and Technology, 2024)
Dialectology is the research of dialects, which are varieties of a language that differ in pronunciation, vocabulary, and sometimes grammar. It explores regional, social, and historical variations within a language, aiming to understand how and why these differences occur . This paper has its focus on studying the difference between the regional language and standard language. The data is collected by using various recording devices and mobile phones. The primary goal of this paper is to explore how language changes in different situations. The focus is on examining variations in language usage, especially the choice of words (vocabulary), across various contexts. By carefully analyzing these linguistic differences, the study intends to offer valuable insights into understanding the specific context in which an individual is communicating. This can shed light on how language adapts to different environments and provides a deeper understanding of communication patterns. Analysis of dialects can help identify the geographic or social origin of a speaker, providing insights into their background. This can be useful in cases where the origin of a suspect or victim is uncertain. Linguistic experts may analyze speech patterns, vocabulary, and pronunciation to draw conclusions about a person's likely dialect, contributing to the overall forensic investigation
Keywords: Dialects; Vocabulary; Historical Variations; Recording Devices; Linguistic; Linguistic Experts; Forensic Investigation